2012
DOI: 10.1136/neurintsurg-2012-010304
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular recanalization for chronic symptomatic middle cerebral artery total occlusion

Abstract: The optimal treatment of chronic middle cerebral artery (MCA) occlusion is unclear. Angioplasty and stenting may be an alternative treatment for patients with recurrent ischemic symptoms despite medical therapy. Two patients with chronic right MCA occlusion successfully treated with stenting are reported, together with their long term follow-up to illustrate the feasibility of endovascular recanalization. One patient remained asymptomatic at the 29-month follow-up. Another patient developed symptomatic in-sten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…3 Therefore, intracranial angioplasty and stent placement have been recommended to reduce the rate of recurrent ischemic events. [4][5][6][7] However, the Stenting versus Aggressive Medical Management for Preventing Recurrent Stroke in Intracranial Stenosis (SAMMPRIS) trial 8 was prematurely terminated due to excessively high 1-month stroke and/or death rates in patients randomized to intracranial stent placement. At the time of the Data Safety Monitoring review, 14.7% of patients treated with angioplasty combined with stent placement experienced a stroke or died within 1 month after enrollment compared with 5.8% of patients treated with medical therapy alone, a highly significant difference.…”
mentioning
confidence: 99%
“…3 Therefore, intracranial angioplasty and stent placement have been recommended to reduce the rate of recurrent ischemic events. [4][5][6][7] However, the Stenting versus Aggressive Medical Management for Preventing Recurrent Stroke in Intracranial Stenosis (SAMMPRIS) trial 8 was prematurely terminated due to excessively high 1-month stroke and/or death rates in patients randomized to intracranial stent placement. At the time of the Data Safety Monitoring review, 14.7% of patients treated with angioplasty combined with stent placement experienced a stroke or died within 1 month after enrollment compared with 5.8% of patients treated with medical therapy alone, a highly significant difference.…”
mentioning
confidence: 99%
“…Aghaebrahim et al indicated that the rate of successful recanalization was 100% in four patients after PTAS, but one patient developed symptomatic ICH and only two patients achieved an mRS score of 0–2 (7). Ma et al reported two successful stenting procedures, with one patient developing recurrent TIA and 80% restenosis (8). In our study, although only seven cases underwent stent placement after angioplasty, showing a lower percentage of stenting compared to that in previous studies (7, 16, 17), our team achieved a high rate of revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al reported two cases of chronic symptomatic MCA occlusion treated with angioplasty and stenting; the long-term outcomes were acceptable, suggesting that endovascular treatment for chronic symptomatic MCA total occlusion is feasible, despite the potential risk of severe complications. 102 Recently, a retrospective study described the safety and feasibility of continuous indirect encephaloduroarteriosynangiosis (EDAS) bypass in anterior circulation arterial steno-occlusion. 103 Although the outcomes only provide initial evidence and further studies are required to confirm the results, this research provided an optional treatment for patients with ICAS who fail with medical or endovascular therapy.…”
Section: Treatmentmentioning
confidence: 99%